Evaluating the Price, Availability, and Affordability of Essential Medicines in Primary Healthcare Institutions: A Mixed Longitudinal and Cross-Sectional Study in Jiangsu, China - Wang, Xiao; He, Xuan; Ren, Yuqin; Zhang, Zhuolin; Cai, Lele; Cao, Zhaoliu; Li, Xin (Frontiers in Public Health, 2022)
Objective: This study aimed to evaluate the price, availability, and affordability of essential medicines in primary healthcare institutions in Jiangsu Province. Methods: A mixed longitudinal and cross-sectional survey was conducted in primary healthcare institutions in Jiangsu based on the adjusted World Health Organization and Health Action International methodology. 45 essential medicines were collected from 30 primary healthcare institutions in Nanjing from 2016 to 2020. We also collected information on these medicines in 70 primary healthcare institutions in seven cities of Jiangsu in 2021. The availability, price, and affordability were compared with matched sets. Differences of availability between years and cities were further compared using Wilcoxon rank-sum test. Results: In Nanjing, the variation was significant of availability during the study period. The MPR was generally decreasing between 2016 and 2020, with the median price ratio (MPR) for lowest-priced generics (LPGs) ranging from 1.20 to 2.53 and originator brands (OBs) substantially above international levels. The median availability of generic medicines increased in 2018 and subsequently stabilized at around 55%, and the availability of originator medicines was low. There were no significant regional differences in prices across the sampled cities in Jiangsu, and the median MPR for LPGs was acceptable (1.23), while the median MPR for OBs was 8.54. The mean availability rate was different across regions(p<0.001), it was higher in Nanjing (54.67%) and Nantong (56.22%), and lower in northern Jiangsu (about 35%). For LPGs, there was little difference in the proportion of medicines with low availability and high affordability (50.00% for urban residents and 40.48% for rural residents). For OBs, there were more than half of rural residents had low availability and low affordability of medicines (58.82%). Conclusions: In terms of yearly changes, the prices of essential medicines have considerably decreased, and the availability of LPGs has slightly increased. However, the availability of medicines was found to be poor and there were regional differences in the availability and affordability of medicines among metropolitan and rural areas. Policy interventions targeting external factors associated with health resource allocation are essential and possible strategies include effective and efficient government investment mechanisms on primary healthcare.